Zgrupowania nietoperzy w rozdrobnionych kompleksach leśnych w okolicy Rogowa (środkowa Polska) - Lesiński, Grzegorz; Gryz, Jakub; Krauze-Gryz, Dagny; Rachwald, Alek (Leśne Prace Badawcze, 2018)
Habitat fragmentation affects bat assemblages living in forests by changing species composition, species richness and population densities. The aim of this paper was to determine the structure of bat assemblages in fragmented forests of central Poland (Experimental Forest Station SGGW in Rogów) based on data concerning bat fauna of this area. Our work is based on published as well as unpublished data collected between 2011–2017 and the two main methods employed during field work were: (1) evening and night bat netting, (2) detection of flying bats on transects or in points by using ultrasound detectors. 16 bat species were observed with the most common ones being serotine bat Eptesicus serotinus (Schreb.), common noctule Nyctalus noctula (Schreb.) and brown long-eared bat Plecotus auritus (L.). Less numerous in overall but frequently observed in some sites were the western barbastelle Barbastella barbastellus (Schreb.) and the Daubenton’s bat Myotis daubentonii (Kuhl). The following species occurred rarely: greater mouse-eared bat Myotis myotis (Bork.), Natterer’s bat M. nattereri (Kuhl), whiskered bat M. mystacinus (Kuhl), Brandt’s bat M. brandtii (Evers.), Northern bat Eptesicus nilssonii (Keys. & Blas.) parti-coloured bat Vespertilio murinus L., lesser noctule Nyctalus leisleri (Kuhl), common pipistrelle Pipistrellus pipistrellus (Schreb.), Nathusius’ pipistrelle P. nathusii (Keys. & Blas.), soprano pipistrelle P. pygmaeus (Leach) and grey long-eared bat Plecotus austriacus (Fish.). Fragmented forests of the study area did not differ significantly in terms of bat species composition from other fragmented forests of central Poland (Płońsk Plain) nor the large forest complexes of the Bolimowska and Kampinoska Forests. In this study area, however, bat assemblages were characterized by a lower relative abundance of the common noctule and a higher relative abundance of the serotine bat as compared to assemblages in other forests of central Poland. In conclusion, the forest fragmentation near Rogów does not significantly affect bat richness and fertilized habitats are suitable for relatively large populations of species such as the western barbastelle and lesser noctule.